The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2018
DOI: 10.15448/1980-6523.2017.4.28957
|View full text |Cite
|
Sign up to set email alerts
|

Prevention and early diagnosis of oral cancer – a literature review

Abstract: INTRODUCTION: The present study identified and described scientific production on primary and secondary prevention of oral cancer worldwide. This is an integrative review of the literature, focusing on the description of oral cancer prevention experiences.METHODS: The search was performed in the Virtual Health Library (VHL), using the descriptors: early diagnosis, oral neoplasms, primary prevention and secondary prevention. We found 225 articles and selected 22 after evaluation, divided into three themes.RESUL… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 23 publications
0
2
0
Order By: Relevance
“…It has the advantages of being painless, harmless, noninvasive, and low-cost. As for disadvantages, it does not have the same efficacy as biopsy concerning identifying the type of lesion, but it is beneficial when the biopsy is not possible [20,28,29].…”
Section: Exfoliative Cytologymentioning
confidence: 99%
See 1 more Smart Citation
“…It has the advantages of being painless, harmless, noninvasive, and low-cost. As for disadvantages, it does not have the same efficacy as biopsy concerning identifying the type of lesion, but it is beneficial when the biopsy is not possible [20,28,29].…”
Section: Exfoliative Cytologymentioning
confidence: 99%
“…However, a study by showed that the difficulties encountered about the device and the anatomical structures examined (lip and oral cavity) were related to the contact of the lens surface, fine tremors, and the sliding of the device; these difficulties varied according to topography. The quality depended on the site of the lesion, the extent of the ulceration, the volume of crusts, prior cleaning of the site, patient collaboration, the presence of more or less saliva, the mobility of the examined structure, and the support for the device [28,30].…”
Section: Contact Endoscopymentioning
confidence: 99%